Proses Pembelajaran Daring Masa Pandemi pada Guru SMP Islam Azzhahiriyah - Mutmainah Mutmainah (Neolectura, 2022)
The Covid-19 pandemic has greatly affected the world of education today so that one of the impacts is that the government in Indonesia has implemented a policy to carry out online-based distance learning which is called online learning. This study aims to determine the extent to which Azhahiriyah Islamic Middle School teachers utilize information technology in the distance learning process, the supporting factors and factors that hinder teachers while carrying out online learning during the pandemic. The method used in this study was descriptive qualitative method, with data collection techniques based on open questionnaires, field notes, teacher learning documents and interviews where the subjects in the study were junior high school teachers at SMP Islam Azzhahiriyah Bekasi. Online learning requires students to continue to study face-to-face virtually or be present in person but not physically, so that the use of information technology greatly supports learning methods during the Covid-19 Pandemic. With the advancement of information technology at this time, the internet is a basic requirement so that teachers can always be connected with students during online learning through the hybrid course method or blended learning using e-learning, virtual class video conferencing, and social media. During the online learning process students study at home while still being monitored by parents and teachers. The supporting factors that underlie teachers can carry out the online learning process are by using media such as Zoom meetings and WA Groups. Then the teacher has utilized online learning technology using zoom meetings for distance learning and Google Classroom to collect assignments. supporting factors there are also factors that hinder teachers in online learning, factors that can hinder them include not all students have gadgets, limited quotas and not all parents are able to accompany students to study at home